EVALUASI RISIKO CELAH KEAMANAN MENGGUNAKAN METODOLOGI OPEN-SOURCE SECURITY TESTING METHODOLOGY MANUAL (OSSTMM) PADA APLIKASI WEB TERBARU FAKULTAS ILMU KOMPUTER UPN VETERAN JAKARTA - Akmal Ilmi (2022)
The development of web application-based technology has grown rapidly in recent years so that it is used in various sectors, one of which is the university sector. However, this development is inseparable from the big issues and dangers of Information security on the higher education sector web. As in the latest website of the Faculty of Computer Science, UPN Veterans Jakarta, with the domain http://new-fik.upnvj.ac.id. To prevent this, a comprehensive evaluation of the risk of vulnerabilities on the web is needed. The method used in that study is the OSSTMM method, it can test how high the security level of a web application is with RAV and STAR ratings. This method is expected to get benefits and outputs in the form of recommendations that must be made to IT and web developers of the new Faculty of Computer Science UPN Veteran Jakarta.